Analyzing Misconceptions Using Four-tier Test on the Topic of Vibration: A Survey of Pre-service Science Teachers - Nanang Winarno; Ratih Mega Ayu Afifah; Rizky Agassy Sihombing; Rohim Aminullah Firdaus; Insar Damopolii (Universitas Negeri Semarang, 2025)
Vibration is one of the essential topics in science education. Pre-service science teachers still often experience difficulties in learning this topic. There are several previous studies related to misconceptions on the topic of vibration. However, research on misconceptions in pre-service science teachers is still limited. This study aimed to analyze pre-service science teachers' misconceptions on the topic of vibration. This research uses a quantitative approach with a survey method. The research instruments include a four-tier test and interviews. The participants in this study consist of 96 pre-service science teachers from a university in Bandung, Indonesia. The results of the analysis showed that pre-service science teachers who had Scientific Knowledge were 31.1%, lack of knowledge 26.9%, misconception 8.0%, false positive 1.8%, and false negative 2.2%. The most common misconception found relates to the relationship between frequency and mass. The perception of pre-service science teachers regarding the four-tier test questions is very easy 0%, easy 6.7%, neutral 36.7%, difficult 53.3%, and very difficult 3.3%. The findings show that many pre-service science teachers still have misconceptions about the topic of vibration so lecturers should strengthen the concepts of Fundamental Physics first before students take advanced physics courses.